Extradition of A Person for Criminal Prosecution: International Law and National Aspects - Iurevich Epihin, Aleksandr (2020)
The article analyzes the scientific and practical problems of the institution of extradition of a person for a criminal prosecution substantiates the importance of this institution and its role in the law enforcement activity of the state. The authors carried out a comparative analysis of the provisions of the fundamental international acts in force and Russian legislation governing extradition issues. At the same time, attention is paid to establish the significance of international treaties and agreements on extradition for cooperation between states in law enforcement. The article focuses on an important circumstance that not only persons who have committed conventional (with increased risk), but also ordinary crimes are subject to extradition.